#TITLE_ALTERNATIVE# - SITANGGANG (NIM 12103062), RUDIANTO
Kuz- Ram is one of method to predict rock fragments distribution as a result of rock blasting. Rock factor as one of input data in Kuz- Ram model, obtained from rock parameters rating that was given by Lily (1986). There are 5 rock parameters to be considered in calculation of rock factor : rock mass description (RMD), joint plane spacing (JPS), joint plane orientation (JPO), specific gravity influence (SGI), and moh's hardness (H). In fact, the values of those parameters are vary between its minimum value to maximum value. To determine the rock factor with the value of rock parameters which vary, used simulation of Monte Carlo. Result of calculation by using simulation of Monte Carlo is total rating for rock parameters. Then, total rating of rock parameters is used to obtain blastability index (BI) and rock factor 7,39. Rock factor, blast geometry, and total charge of explosives are the input data that used for Kuz-Ram model to predict the result of rock blasting. Comparison distribution of rock fragment between result from field perception with the Kuz-Ram model prediction for using ANFO explosives : 5,84% to size of rock fragment < 20 cm; 14,95% to size of rock fragment 20 - 50 cm; 20,79% to size of rock fragment > 50 cm. In other case, comparison distribution of rock fragment between result from field perception with the Kuz- Ram model prediction for using Titan Black explosives : 2,79% to size of rock fragment < 20 cm; 14,02% to size of rock fragment 20 - 50 cm; 16,81% to size of rock fragment > 50 cm. To get the prediction of Kuz- Ram model close to field perception, X and n was corrected by curve fitting method. For using ANFO explosives, correction factor from curve fitting for X is 0,67 and for n is 1,20. For using Titan Black explosives, correction factor from curve fitting for X is 0,73 and for n is 1,26. Distribution of rock fragment as a result of rock blasting from Kuz-Ram model for using ANFO explosives : 21,94% to size of rock fragment < 20 cm; 42,21% to size of rock fragment 20 - 50 cm; 35,86% to size of rock fragment > 50 cm. Distribution of rock fragment as a result of rock blasting from Kuz-Ram model for using Titan Black explosives : 24,63% to size of rock fragmen < 20 cm; 42,86% to size of rock fragment 20 - 50%; 32,51% to size of rock fragment > 50 cm.